2007
DOI: 10.1007/s10762-007-9221-0
|View full text |Cite
|
Sign up to set email alerts
|

Weibull Raindrop-Size Distribution and its Application to Rain Attenuation from 30 GHz to 1000 GHz

Abstract: A weibull raindrop-size distribution is fitted to the measurements of rainfall observed using a distrometer in Tokyo. A propagation experiment at 103 GHz is also introduced. The rain attenuation is calculated by considering the Mie scattering for the Marshall-Palmer, Best, Joss-Thomas-Waldvogel, Gamma and Weibull raindrop-size distributions. The results of frequency characteristics from the Weibull raindrop-size distribution agrees well with some experimental data for the millimeter and submillimeter waves abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…There have been many investigations of THz attenuation based on different raindrop size distributions in outdoor rain conditions [21][22][23][24]. Several empirical raindrop size distributions have been presented such as exponential distribution, log-normal distribution, gamma distribution, and normalized gamma distribution.…”
mentioning
confidence: 99%
“…There have been many investigations of THz attenuation based on different raindrop size distributions in outdoor rain conditions [21][22][23][24]. Several empirical raindrop size distributions have been presented such as exponential distribution, log-normal distribution, gamma distribution, and normalized gamma distribution.…”
mentioning
confidence: 99%
“…To our knowledge, a detailed theoretical study of such 'shot-noise' has not been performed up to now. However, a substantial dispersion of values is visible in the experimental data presented in [16] and [17]. Furthermore, such dispersion can be seen even in the case of the laboratory-controlled rain at extreme 50-400 mm/h rain rates with a relatively narrow Gaussian-like raindrop size distribution [20].…”
Section: Introductionmentioning
confidence: 92%
“…However, this simplified approach is only one of the available alternatives. For example, M. Sekine et al [16] considered the Mie scattering theory for five raindrop-size distributions and determined that the Weibull distribution best describes the rain attenuation above 30 GHz. In a later work it was demonstrated that the Mie scattering theory with Best and P-S distributions provide the most suitable agreement with the experimental values in the 90-225 GHz range, while the ITU-R model and Mie scattering with the Weibull distribution leads to a better approximation at 313 and 355 GHz [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed knowledge of rain drop size densities is an essential presumption with respect to remote sensing of precipitation. Recent research reveals that rain drop size densities can be described either by an exponential distribution (e.g., Marshall and Palmer [1]), a gamma distribution (e.g., Ulbrich and Atlas [2]), or a Weibull distribution (e.g., Sekine et al [3]).…”
Section: Introductionmentioning
confidence: 99%